2006
DOI: 10.1080/07399330600629583
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Care Strategies of Girls with Primary Dysmenorrhea: A Focus Group Study in Taiwan

Abstract: Dysmenorrhea is the most common gynaecological complaint and the leading cause of recurrent short-term school absenteeism among adolescent girls. To explore adolescent girls' self-care strategies for dysmenorrhea, we conducted four focus groups in Kaohsiung, Taiwan, with 23 female adolescents with primary dysmenorrhea. Thematic content analysis was used to explore and organize the data. The self-care strategies for dysmenorrhea reported by participants included reducing physical activity, modifying diet using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
9
27
0
1
Order By: Relevance
“…It has been reported that women were reluctant to consult a physician because they viewed it as "part and parcel" of female life and they should selfmanage the symptoms, while some did not think the physician could do much to help [34]. We found many participants used self-care strategies and lifestyle management techniques to relieve the symptoms of PMS, which was consistent with other findings [34,35]. The reason for the low rate of consulting a physician for PMS among the Chinese participants could be due to beliefs in the efficacy of traditional Chinese medicine and its common uses for PMS and dysmenorrhea [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that women were reluctant to consult a physician because they viewed it as "part and parcel" of female life and they should selfmanage the symptoms, while some did not think the physician could do much to help [34]. We found many participants used self-care strategies and lifestyle management techniques to relieve the symptoms of PMS, which was consistent with other findings [34,35]. The reason for the low rate of consulting a physician for PMS among the Chinese participants could be due to beliefs in the efficacy of traditional Chinese medicine and its common uses for PMS and dysmenorrhea [35].…”
Section: Discussionsupporting
confidence: 92%
“…We found many participants used self-care strategies and lifestyle management techniques to relieve the symptoms of PMS, which was consistent with other findings [34,35]. The reason for the low rate of consulting a physician for PMS among the Chinese participants could be due to beliefs in the efficacy of traditional Chinese medicine and its common uses for PMS and dysmenorrhea [35]. Another study has reported that women who were older and with more severe PMS symptoms were more likely to seek treatment [36].…”
Section: Discussionsupporting
confidence: 82%
“…For instance, they believed that these foods not only ''enhanced qi circulation' ' but also ''enriched the blood, ' ' and thus helped to relieve the condition. Nevertheless, unlike girls in a Taiwanese qualitative study who were reported to consume Chinese herbal remedies such as Zhongjiang herbal soup and Xiaoyao powder for dysmenorrhea (Chen et al, 2006), the girls in this study did not mention using such herbal remedies, although it is noteworthy that they believed herbal remedies should only be prescribed by a Chinese medicine practitioner. They would not buy or consume herbal remedies without a consultation.…”
Section: Self-care Strategies Among Adolescent Girls With Dysmenorrheamentioning
confidence: 70%
“…However, studies on such self-care have been largely quantitative-only one qualitative study was found describing it in adolescent girls. Chen, Lin, Heitkemper, and Wu (2006) brought together four focus groups from among 23 Taiwanese nursing students aged 16 to 19 to explore their experiences of self-care for dysmenorrhea. Seven themes emerged: reducing physical activity, modifying diet, using herbal remedies or medication, applying complementary therapies, paying attention to symptom clusters of discomfort, and expressing emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In academic life, students tended to be absent from school, unable to focus on their courses, and distracted from lectures due to dysmenorrheal symptoms. 16,17,33 Other studies also confirm female adolescents' negative attitudes toward education 3,29,37 and absenteeism was common due to excessive pain 25 and other discomforting symptoms. 9,18,33 One third of the subjects with dysmenorrhea reported absenteeism from school because of their pain.…”
Section: Discussionmentioning
confidence: 86%